Problems and Support Needs of Beginning Teachers during the First Years in the Profession - Barkauskaitė, Marijona; Habil; Meškauskienė, Asta (European Journal of Social Science Education and Research, 2018)
The article deals with the challenges that new teachers experience in the first years of their profession while dealing with students’ educational issues. With the help of quantitative and qualitative research methods the article aims to establish the main reasons identified by the beginning teachers for the problem situations to occur and to assess the need for assisstance and support at the beginning of their teaching careers. The study allowed to establish the areas of the professional work where the following difficulties were experienced: in individualizing the learning and teaching processes, in working with students who have special educational needs; in cooperating with parents, in motivating students to learn and others. The standardized interview with school heads revealed that the difficulties experienced by the beginning teachers during their first years in the profession and the need for assistance is neither addressed by school headmasters nor by school communities. Keywords: beginning (novice/ new) teachers, profession related problems, the need for support, mentors